EDITORIAL BOARD - *, * (Philippine Engineering Journal; Vol 37 No 1 (2016), 2016)
The PHILIPPINE ENGINEERING JOURNAL serves as a national medium of exchange of technical information and dissemination of engineering knowledge through the publication of technical papers, technical notes, and research briefs. Published by the U.P. Engineering Research and Development Foundation, Inc. for the National Engineering Center, the PHILIPPINE ENGINEERING JOURNAL is being distributed at reasonable rates to various government agencies, private industrial concerns, engineering schools, professional organizations, international entities and practitioners in the field of engineering.